UMPSA researcher, Dr. Agi, petroleum engineering expert, aspires to win Nobel Prize - Naqiah, Puaad (UMPSA, 2025)
GAMBANG, 10 February 2025 – Dr. Agi Augustine Aja, a senior lecturer at the Faculty of Chemical and Process Engineering Technology (FTKKP), Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA), has shared his dream of winning the prestigious Nobel Prize at the international level. Dr. Agi Augustine Aja, who is among the top 2% of scientists worldwide, according to Elsevier and Stanford University, expressed confidence that his dream will come true one day.